Nonlinear Relationship Between Macrocytic Anemia and Decompensated Hepatitis B Virus Associated Cirrhosis: A Population-Based Cross-Sectional Study - Tian-Yu Zhao; Qing-Wei Cong; Fang Liu; Li-Ying Yao; Ying Zhu (Frontiers Media S.A., 2021)
Background: Mean corpuscular volume (MCV) is major used as an indicator for the differential diagnosis of anemia. Macrocytic anemia in decompensated cirrhosis is common. However, the relationship between macrocytic anemia and decompensated hepatitis B virus (HBV) associated cirrhosis has not been fully addressed.Methods: In this cross-sectional study, a total of 457 patients diagnosed decompensated HBV associated cirrhosis who met all inclusion criteria from 2011 to 2018 were analyzed. Association between macrocytic anemia and the liver damaged (Model for End Stage Liver Disease (MELD) score) were examined using multiple logistic regression analyses and identified using smooth curve fitting.Results: Compared with normocytic anemia, MCV and MELD are significantly positively correlated in macrocytic anemia (p < 0.001). A non-linear relationship of MCV and MELD association was found though the piecewise linear spline models in patients with decompensated HBV associated cirrhosis. MCV positive correlated with MELD when the MCV was greater than 98.2 fl (regression coefficient = 0.008, 95% CI 0.1, 0.4).Conclusion: Macrocytic anemia may be a reliable predictor for mortality because it is closely related to the degree of liver damage in patients with decompensated HBV associated cirrhosis.